Geothermal source heat pumps under energy services companies finance scheme to increase energy efficiency and production in stockbreeding facilities. (August 2015) - Borge-Diez, David; Colmenar-Santos, Antonio; Pérez-Molina, Clara; López-Rey, África
Abstract: In Europe energy services are underutilized in terms of their potential to improve energy efficiency and reduce external energy dependence. Agricultural and stockbreeding sectors have high potential to improve their energy efficiency. This paper presents an energy model for geothermal source heat pumps in stockbreeding facilities and an analysis of an energy services business case. The proposed solution combines both energy cost reduction and productivity increases and improves energy services company financing scheme. CO2 emissions drop by 89%, reducing carbon footprint and improving added value for the product. For the two different evaluated scenarios, one including winter heating and one including heating and cooling, high IRR (internal return rate) values are obtained. A sensitivity analysis reveals that the IRR ranges from 10.25% to 22.02%, making the investment attractive. To make the research highly extensible, a sensitivity analysis for different locations and climatic conditions is presented, showing a direct relationship between financial parameters and climatic conditions. A Monte Carlo simulation is performed showing that initial fuel cost and initial investment are the most decisive in the financial results. This work proves that energy services based on geothermal energy can be profitable in these sectors and can increase sustainability, reduce CO2 emissions and improve carbon footprint. Graphical abstract: Highlights: Geothermal heat pumps are studied to promote industrial energy services. Geothermal energy in farming facilities improves global competitiveness. Research shows profitability of low enthalpy geothermal energy services. Climatic conditions sensitivity analysis reveals IRR ranges from 10.25% to 22.02%. Added market value for the product as carbon footprint reduction, are achieved.